PARAFFIN: A software tool for Pathology Report Automated Feedback for Improved Education of anatomic pathology trainees - Clarissa E. Jordan; Justin E. Juskewitch; Andrew P. Norgan (Journal of Pathology Informatics)
Background: Feedback on the diagnosis and reporting of pathology findings is essential to the training of residents and fellows, but time constraints and other factors can make it difficult to ensure learners are made aware of the outcome of all cases in which they participated. Many trainees attempt to keep track of their cases and later look up final pathology reports in the laboratory information system (LIS); however, this manual and time-consuming process is prone to error and may prevent them from spending time reviewing and learning from these reports. Methods: To address this, we developed a software solution, (Pathology Report Automated Feedback for Improved Education; “PARAFFIN”), which provides pathology trainees with a weekly email digest containing an attached case log with the date, accession sequence, attending pathologist initials, and final diagnosis text for each case in which they participated. PARAFFIN is implemented as two R scripts running on a Posit Connect server: a data extraction script, which accesses an interactive report from our enterprise analytics SQL server, and a reporting script, which performs recipient-specific filtering and emails the trainee with their personalized case log attached as .txt and .csv files. After implementation, pathology trainees were surveyed about PARAFFIN's impact on report collection and case feedback. Results: Of the total 51 pathology trainees who were receiving PARAFFIN digests at the long-term follow-up timepoint, 20 responded to our survey. 90% (18 of 20) of respondents report that PARAFFIN allows them to spend more time reviewing the content of final anatomic pathology reports, rather than collecting reports. Trainees report utilizing PARAFFIN for feedback on multiple aspects of pathology reporting, with final diagnosis, wording/style of final diagnostic line, and diagnostic comment being most frequently used. Conclusions: Our automated case feedback solution provides trainees with a record of final pathology reports for cases in which they participated, which allows trainees to spend more time reviewing reports for feedback rather than manually collecting them from the LIS.